Menara Yayasan Selangor / Muhammad Shaiful Nezam Lokman ... [et al.] - Muhammad Shaiful Nezam, Lokman; Muhammad Zuhdi, Ahmad; Norman, Frankie; Nur Athirah Fatin, Mohayidin; Najihah Mahfuzah, Mazlan (2019)
In Diploma of Building Surveying, the report of Integrated Final Project is the most important for student of building surveyor which it is the core subject for the final year student of Building Surveyor. This report required a group of students to study and analyze the organization management and the building management of a case study building. At the end of the study the students will able to know how a building can be manage through its organization and their maintenance management. This project consists of nine chapter. For the first chapter we will tells about the background of the organization and building and its occupants. For the Chapter 2, we will discuss about the main organization and the maintenance organization. Inthis chapter we will able to know their roles and its responsibility to the building. For the chapter 3, we will full described about maintenance policy, planning and programme at the case study. From this it can be conclude that the building is fully organized and have a proper maintenance planning to keep the building function well. Chapter 4 will cover about the building design and concept of the building and also the special features, building services and facilities, external works and also the special technologies and features that implemented in the building. Next, Chapter 5 will discuss about the building condition assessment of the building. We will analyze the defect and its rectification cost. Moving to the chapter 6, we will describe on details about how the maintenance strategy implemented to the building. Then, in the chapter 7, student have to analyze the legal aspect that implemented to the building. In this chapter we will see the how the tenant occupied in the building. we also have to identify the budget of the maintenance for the building. And determine the forecast budget for the organization in 3 years ahead. Lastly, in chapter 9, we will identify the problem from the chapter 1 to the chapter 8 and make the recommendation from the problem. From the overall chapter that covered of the building, student have to make its conclusion.